Effect of organic fertilizer on the development of tomatoes and behavior metals in soil within the forest-steppe zone of Ukrainian - Гарбуз, А. Г. (Man and Environment. Issues of Neoecology, 2014)
There are the results of investigation of the influence of the form of organic fertilizers on biometrics vegetables (tomatoes for example) and the behavior of metals in the soil. The study was conducted in Kharkiv and Cherkasy regions. Оn experimental plots where made fertilizers, was an increase in the height and thickness of the tomato plant stems at the base of the bush, and the number of inflorescences . It was determined that the soil has decreased the amount determined by the mobile forms of metals. It was determined that the most «environmentally safe» fertilizer include Scots pine litter and worm castings , where the content of mobile forms of metals smallest .